Torção uterina em gata: relato de caso - Menezes, Karlyson Kleber Santos (2022)
This report was prepared as a requirement for obtaining a bachelor's degree in Veterinary Medicine from the Federal University of Sergipe - Campus do Sertão, and was developed during the Mandatory Supervised Internship (ESO), which was carried out at the Popular Recanto Animal Clinic, veterinary clinic located in the city of Aracaju, Sergipe. The internship activities focused on the observation and monitoring of care provided in the clinical and surgical areas. The activities developed are described in this document, and for the course conclusion work (TCC) a clinical case of the theme “uterine torsion in a cat” was described, which follows with a literature review on the subject.